Potent anti-Toxoplasma gondii activity of 4-chlorophenylthioacetone-derived thiosemicarbazones: Involvement of CCR2 and CCR5 receptors and 5-lipoxygenase in the mode of action - Rayane Aparecida Nonato Rabelo; Diego Rodney Rodrigues de Assis; Alexandre Almeida Oliveira; César Luís Nascimento Barbosa; Rafaela das Dores Pereira; Ricardo Wagner de Almeida Vitor; Wiliam César Bento Régis; Mauro Martins Teixeira; Heloísa Beraldo; Fabiana Simão Machado (Elsevier, 2023)
Toxoplasmosis is a disease requiring therapeutic innovation, and thiosemicarbazones with antimicrobial activity are candidates to control Toxoplasma gondii infection. Here, the anti-T. gondii activities of (E)-2-(1-(4-chlorophenylthio)propan-2-ylidene)-hydrazinecarbothioamides (Ca and Cb) were investigated. T. gondii-infected macrophages (MOs) or glial cells treated with Ca or Cb showed a decrease in the number of intracellular parasites. A deficiency in the chemokine receptor CCR2, but not CCR5, partially reduced anti-T. gondii activity induced by Ca or Cb. In contrast, a deficiency in 5-lipoxygenase (5-LO) activity potentiated anti-T. gondii activities induced by these compounds. In vivo treatment with Ca increased the survival of T. gondii-infected wild-type mice, and this was associated with increased IFN-γ and IL-12 production. A deficiency in CCR5 or CCR2 abolished the protective effect of Ca treatment in vivo, while a deficiency in 5-LO increased Cb anti-T. gondii effects. Collectively, our data suggest that Ca and Cb are potential therapeutic candidates for the treatment of toxoplasmosis.